2020
DOI: 10.3390/app10238390
|View full text |Cite
|
Sign up to set email alerts
|

Novel Human-in-the-Loop (HIL) Simulation Method to Study Synthetic Agents and Standardize Human–Machine Teams (HMT)

Abstract: This work presents a multi-year study conducted at the University of Toledo, aimed at improving human–machine teaming (HMT) methods and technologies. With the advent of artificial intelligence (AI) in 21st-century machines, collaboration between humans and machines has become highly complicated for real-time applications. The penetration of intelligent and synthetic assistants (IA/SA) in virtually every field has opened up a path to the area of HMT. When it comes to crucial tasks such as patient treatment/care… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In accordance with different literature, such as, 38 , 39 and, 40 we highlight and identify different key components and relevant aspects of the integration of HAT in applied settings. Additionally, HAT components and aspects can also serve as a guide for human-autonomy interaction/teaming experiments to inform appropriate methodologies.…”
Section: Key Components and Aspects Of Human-autonomy Teamingsupporting
confidence: 66%
“…In accordance with different literature, such as, 38 , 39 and, 40 we highlight and identify different key components and relevant aspects of the integration of HAT in applied settings. Additionally, HAT components and aspects can also serve as a guide for human-autonomy interaction/teaming experiments to inform appropriate methodologies.…”
Section: Key Components and Aspects Of Human-autonomy Teamingsupporting
confidence: 66%
“…Li, et al [72] further substantiate this by showing that complementary policy adaptation enhances team performance. Damacharla, et al [73] have outlined guidelines for effective HAT composition, including role identification, rule establishment, and specialized training for human members, etc.…”
Section: B Compositional Factorsmentioning
confidence: 99%
“…Common models often look at individual contributions, the overall team setting, and both individual and collective group performance [73]. Our review has identified as many as 28 different dimensions used to measure HAT performance, including commonly used measurements such as team effectiveness, task performance, mission performance, mission success, human workload, average efficiency, and performance perception.…”
Section: Team Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent achievements in natural language processing have allowed the design of human-machine interaction systems through natural language. Some research directions related to the human-inthe-hoop stream can be mentioned, such as improving collaboration between humans and machines [56] and the interaction between humans and agents in the context of a smart city [57].…”
Section: Human-in-the-loop In Masmentioning
confidence: 99%